Investigation of the effects of recreational rowing exercises on physical fitness and quality of life in prostate cancer patients - Türker, Murat (2023)
The aim of the study is to investigate the effects of recreational rowing exercises on cancer patients, who have undergone prostate treatment, on their physical fitness and quality of life. A total of 37 participants (mean age of 59.10± 9.67 years) who completed their prostate cancer (PC) treatments and had no disability to exercise and participated in the recreational sea rowing program were included in the study. The study is consisting of two groups. The participants who refused to participate exercise (n=17 mean age 57.17±13.33 years) are Control Group (CG) and who accepted to join sea rowing program are Exercise Group (EG) (n=19 mean age 59.10 ±9.67 years). The program was carried out 3 days a week for 12 weeks, with an average of 60 minutes per day. Anthropometric measurements (height, weight, circumference measurements, BMI), VO2max and strength measurements were taken at the beginning and end of the program. Quality of life was assessed (EORTC-QLQ-C30 scale) and prostate cancer-specific module (EORTC QLQ-PR25) test. Since the data did not show normal distribution in the statistical analysis, centrality and prevalence criteria were determined for the continuous variables in the analysis, the Wilcoxon test was used for the differences between the pre-test and post-test measurements of the participants, and the Mann Whitney U test was used to determine the differences between the two groups. Statistically significant differences were found in physical fitness; arm thickness, one mile walking, peak force, 1000 m walking, strength and VO2max values (p<0.05). In the comparison of the two groups; Forearm thickness, upper leg circumference, lower leg circumference, average strength (kg), peak force (kg), average power (watt), Vo2max values were found significantly different (p<0.05).According to the result of EORTC-QLQ-C30; When the EG was compared with the pre-test, post-test and CG, a significant difference was found in the parameters of physical function, grip function, fatigue and constipation (p<0.05). According to EORTC QLQ-PR25 results, there was a significant difference in the urinary symptoms and sexual functioning sub-dimensions between the exercise and control groups (p<0.05).As a result of recreational sea rowing exercise, it was observed that the quality of life of the patients increased, the side effects of the disease decreased, aerobic capacity and strength characteristics improved.